Understanding the different pre and post peak adoption drivers in the process of Mobile Social Networking diffusion - Emanuele Giovannetti; Mohsen Hamoudia (International Telecommunications Society (ITS), 2018)
The mobile provision of social networking services including integrated voice, pictures and music over IP lead to the success of companies such as Snapchat, Skype WhatsApp, Twitter or Spotify.. Understanding the rapid international diffusion of these companies' mobile integrated services, resulting from the interplay of consumers' needs and companies' appropriate marketing mixes is of clear managerial relevance, due to the profits and market value implications of the number of customers reached, while being of great research interest, given the complex role played by the different drivers affecting users' adoption decisions for these mobile social networking services. Given the interactive nature of social networking and the ensuing relevance of users' generated content, a member's utility from joining a social networking platform increases with the number of users, so that higher penetration levels increase the utility of new adopters and the expected utility of the potential ones, through direct network externalities (Katz & Shapiro, 1985, 1986). As technological change is constantly transforming and increasing the capabilities of smartphones, allowing mobile Internet access for sharing and transmitting videos, pictures music and voice, and because of the increasingly fast mobile access networks, Mobile Social Networking adoption choices are also affected by indirect network externalities due to the diffusion of smartphones, the complementary commodities required for the adoption of MSN services identified as a key driver for the adoption of mobile applications. Other likely predictors for the adoption decisions are likely to be linked to the effective prices of using mobile phones, a crucial driver for adoption of multimedia mobile services and the time spent on using them.
Keywords: 330; Mobile Social Networking; Diffusion; Early & Late Adopters; Indirect Network Externalities; Penetration Pricing; Interaction Models